Evaluation of the occurrence of sexual dysfunction and general quality of life in female patients with psoriasis - Kurizky, Patricia Shu (2018)
Background: Psoriasis has a significant impact on quality of life (QoL). Sexual life can also be affected, with sexual dysfunction being reported by 25-70% of patients. Objectives: To determine the occurrence of sexual dysfunction and evaluate QoL in women with psoriasis. Methods: This case-control study included women aged 18-69 years. The validated Brazilian Portuguese versions of the Female Sexual Function Index (FSFI) and of the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36) were administered to all participants to assess sexual function and QoL, respectively. Patients with psoriasis underwent clinical evaluation for the presence of comorbidities, especially psoriatic arthritis and other rheumatic manifestations. Location of lesions and the extent of skin involvement were also assessed. Results: The sample consisted of 150 women, 75 with diagnosis of psoriasis and 75 healthy controls. Prevalence of sexual dysfunction was high in women with psoriasis (58.6% of the sample). Prevalence was statistically higher in women with psoriasis than in controls (P = 0.014). The SF-36 domain scores were also lower in women with psoriasis, with role limitations due to physical health, limitations due to emotional problems, and mental health being the most affected domains. Study limitations: Sample size was calculated to evaluate the association between the occurrence of sexual dysfunction and psoriasis, but it did not include the determination of the possible causes of this dysfunction. Conclusions: QoL and sexual function were altered in women with psoriasis and should be taken into consideration when assessing disease severity.